THE RELATIONS BETWEEN URBAN PARKS AND PERSONAL WELL-BEING IN BRISBANE, SOUTH-EAST QUEENSLAND, AUSTRALIA - Hoàng Công Trí; Nguyễn Thanh Hùng; Muhammad Kamal (Faculty of Geography, Universitas Gadjah Mada, 2012)
The positive impacts of urban parks on human health have been analysed in many studies,but nearly none of them provide a suitable method to explain quantitatively the satisfactionand dissatisfaction of park uses on personal health. Bayesian Belief Network (BBN) wasemployed to examine individually well-being spirit in relation to the changes of quality ofparks and the joyfulness on access to parks. This study aims to find answers for questions‘why and where are people happy or unhappy with their health in connections to urbanparks?’ The data for Brisbane area were extracted from the quality of life survey in South-East Queensland, Australia. 70% data was used for learning model parameters; the rest wasfor model testing. The generated model had 73.17% accuracy, and it was imported to ArcGISfor constructing probabilistic maps. Due to the high density of sample points, InverseDistance Weighted (IDW) interpolation was chosen to illustrate the probable happiness andunhappiness on personal health. The result shows that quality of urban parks controlledstrongly the fulfilment of personal health. Local governors can successfully enrich the qualityof urban lives by improving the quality of parks in some specific regions.